Gender compatibility and drive for muscularity among adolescent boys: Examining the indirect effect of emotion regulation difficulties. (December 2021) - Roche, Claudia; Trompeter, Nora; Bussey, Kay; Mond, Jonathan; Cunningham, Mitchell L.; Murray, Stuart B.; Lonergan, Alexandra; Mitchison, Deborah
Highlights: Adolescent boys low in gender compatibility report heightened emotion regulation difficulties. Emotion regulation difficulties are linked with heightened drive for muscularity. Emotion regulation difficulties link gender compatibility with drive for muscularity. Abstract: The drive for muscularity continues to be a prominent concern among adolescent boys. However, it is unknown how gender compatibility (gender typicality and gender contentedness) relates to this pursuit. The present study sought to examine the link between gender compatibility and drive for muscularity among male adolescents, and whether this is partially accounted for by emotion regulation difficulties. Participants were 903 male adolescents, aged 11–19 years, who completed self-report measures as part of the EveryBODY study. Using path analysis, a proposed mediation model was assessed, testing an indirect pathway of gender compatibility and drive for muscularity through emotion regulation difficulties. Findings showed an indirect pathway between gender compatibility and drive for muscularity through emotion regulation difficulties. That is, boys who were more content with their male gender and believed they were typical of their gender reported fewer emotion regulation difficulties and, in turn, exhibited a lower drive for muscularity. Findings support theoretical perspectives integrating masculinity and muscularity in boys, in that those who feel less compatible with their masculinity could be susceptible to developing a greater drive for muscularity to regulate distress deriving from perceptions of not being sufficiently masculine. This study sets the groundwork for future longitudinal studies.